Effectiveness of combined physical exercise and cognitive training in older adults with cognitive impairment: A systematic review and meta-analysis - Wati, Dwi NK.; Lin, Heng Y.; Wang, Jing J. (Narra J, 2024)
Falls among cognitively impaired older adults are a global concern. The aim of this study was to assess the efficacy of combining physical exercise and cognitive training to improve balance among older adults. A systematic search of databases, including Embase, Medline-OVID, CINAHL-EBSCOhost, and Central-Cochrane Library, was conducted from March 9 to April 6, 2023. The search used keywords based on the PICO question, where the population was older adults with cognitive impairment. Compared to a single therapy, the intervention involved a combination of muscle strengthening and cognitive therapy, with the outcome of falls or balance. Inclusion criteria were randomized controlled trials (RCTs) in any setting. Studies with participants under 60 years old and lacking baseline clinical assessments were excluded. EndNote 20 was used as a reference manager tool, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 flow diagram was used to map out the number of identified records. Two investigators worked independently, and the Jadad scale was used for critical appraisal. The PROSPERO registration number is CRD42023454876. A fixed-effects meta-analysis was performed using an inverse-variance method. Four articles met the inclusion criteria, three of which were included in the meta-analysis. Studies were from Europe, New Zealand, and the Philippines, with a total sample of 255 participants and mean ages of 65.9–87.5 years. The studies used combined physical and cognitive training in one group. Results showed a significant moderate effect size (effect size (ES): 2.29; standardized mean difference (SMD): 0.41; p<0.05; heterogeneity (I2): 0%) indicating no heterogeneity. In conclusion, the combined intervention displayed the potential to improve balance for cognitively impaired older adults.